Nonvolatile all-optical 1 × 2 switch for chipscale photonic networks - Stegmaier, M; Ríos, C; Bhaskaran, H; Wright, C; Pernice, W (Wiley, 2017)
Integrated chip-level photonics has the potential to revolutionize future computer systems by eliminating the “von-Neumann information bottleneck” and the power losses resulting from the use of electrical interconnects. Yet, the need for optical-to-electrical conversion has so far hindered the implementation of chip-level all-optical routing schemes, which remain operational without continuous power consumption. Here, a crucial component to successful implementation of such all-photonic networks is demonstrated – an effective, practicable all-optical nonvolatile switch. Current integrated all-optical switches require constant bias power to operate, and lose their state when it is removed. By contrast, our switch is entirely nonvolatile, with the direction of light flow altered by switching the phase state of an embedded phase-change cell using 1 ps optical pulses. High on/off switching contrast devices are achieved that are fully integrated and compatible with existing photonic circuits. It is shown that individual switching events occur with transition times below 200 ps and thus hold promise for ultrafast light routing on chip. The approach offers a reliable and simple route toward hybrid reconfigurable photonic devices without the need for electrical contacting.